1970
DOI: 10.1104/pp.45.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helminthosporium victoriae Toxin on Germination and Aleurone Secretion by Resistant and Susceptible Seeds

Abstract: Oat seeds of cultivars susceptible and resistant to Helminthosporium victoriae were held for various times in pathogen-produced, host-specific toxin solutions; control seeds were in water. Seeds were then washed thoroughly and incubated on moist paper, or dried and stored for 2-3 weeks before germination was attempted. In both cases, germination of susceptible seeds was prevented by previous exposure to toxin for 1 hour or more. Control seeds and treated resistant seeds grew normally. Toxin Several lines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Work by Strobel (1973a;1973b;1974a;1974b; purports to show that sugarcane clones sensitive to HS-toxin produced by Helminthosporium saccharri carry a specific binding protein associated with the plasmalemma. victoriae and HV toxin by Samaddar & Scheffer (1970). The protein was said to be responsible for the transport of Gc-galactosides but its interaction with HS-toxins was considered to disrupt ion transport.…”
Section: Plant Morphologymentioning
confidence: 99%
“…Work by Strobel (1973a;1973b;1974a;1974b; purports to show that sugarcane clones sensitive to HS-toxin produced by Helminthosporium saccharri carry a specific binding protein associated with the plasmalemma. victoriae and HV toxin by Samaddar & Scheffer (1970). The protein was said to be responsible for the transport of Gc-galactosides but its interaction with HS-toxins was considered to disrupt ion transport.…”
Section: Plant Morphologymentioning
confidence: 99%
“…In a study related to chemical regulation of amylase production, Sammaddar and Scheffer (1970) showed that Helminthosporium victoriae toxin blocked gibberellic acid-induced synthesis and secretion of alpha amylase by embryoless seeds of susceptible oats, but not of resistant oats or barley. Their data indicated that the toxin was not a competitive inhibitor of gibbftrpllic acid, but that the blockage of enzyme production may have been an indirect effect.…”
Section: Effects Of Substances Other Than Gibberellic Acidmentioning
confidence: 99%